Cold‐Season Surface Energy Balance on East Rongbuk Glacier, Northern Slope of Mt. Qomolangma (Everest). Issue 6 (14th March 2023) - Liu, Weigang; Yang, Xingguo; van den Broeke, Michiel R.; Huai, Baojuan; Yang, Diyi; Zhang, Dongqi; Qin, Xiang; Yue, Ping; Wang, Heling; Ding, Minghu
Abstract: As the highest peak on the earth, Mt. Qomolangma provides an unparalleled platform to study glacier‐atmosphere interaction. Although glacier surface energy balance (SEB) on Mt. Qomolangma was examined during warm season, relevant knowledge during cold season is still unknown, which prevents a complete understanding of all‐season glacier SEB on it. Based on an in‐situ observation from October 2007 to January 2008, this study presents a cold‐season glacier SEB result at 6, 523 m above sea level on Mt. Qomolangma and identifies its atmospheric control. Our results show that the observational period experienced strong winds and deficient clouds. Near‐surface wind speeds usually exceeded 10 m s −1, resulting in a substantial sensible heat transport toward glacier and thus enhancing outgoing longwave radiation, which, under the combined effect of deficient clouds, eventually caused an increase in longwave radiative loss. The large solar zenith angle and relatively high albedo of the glacier surface led to a small absorption of solar irradiance, which, in combination with the strong longwave radiation loss, resulted in a semi‐permanent surface radiative loss. Uncommon over the highly reflective glacier surface, clouds decreased the incident solar radiation more than increased the longwave radiation, demonstrating that the clouds' shading effect surpassed its greenhouse effect. As a vital heat sink, the turbulent latent heat induced an average sublimation rate of 0.8 mm water equivalent per day. This study provides valuable insights into the atmospheric control on the cold‐season glacier‐atmosphere interaction at high altitudes on Mt. Qomolangma when meteorological variables are subject to the westerlies. Plain Language Summary: Mt. Qomolangma is the highest mountain on the earth. Qomolangma's glacier retreat is a warning sign for rapid climate warming. Understanding the atmospheric control on Qomolangma's glacier mass loss is critical. This paper thoroughly examines how the energy associated with Qomolangma's glacier mass loss at 6523 m above sea level was governed in the cold season. We find that wind speed is an important factor. On one hand, its increase enhanced the energy input toward glacier, increasing surface temperature and thus letting more energy escape from glacier surface under the combined influence of small cloud cover; on the other hand, the increase in wind speed enhanced the mass loss of sublimation, lowering surface temperature. Cloud cover is another factor. The clouds' shading effect of decreasing incoming sunlight surpassed its greenhouse effect of increasing energy toward glacier, making less energy arriving at the glacier surface and thus decreasing mass loss. Additionally, at the highly reflective glacier surface, glacier received weak sunlight in cold season because a significant portion of the relatively modest incoming sunlight was reflected to the sky. These results provide valuable insights into the atmospheric control on Qomolangma's glacier mass loss in the cold season. Key Points: We present 3.5 months of autumn and wintertime glacier surface energy balance at 6, 523 m above sea level on Mt. Qomolangma There was a semi‐permanent surface radiative loss due to deficient clouds, large solar zenith angle, and high albedo of glacier surface Clouds reduced solar irradiance more than increased longwave radiation, implying that their shading effect surpassed the greenhouse effect